Menjadi Guru Inovatif Pada Masa Pandemi: Peningkatan Kapasitas Guru SD Genius Islamic School Kota Depok - Susanto, Susanto (LP2M INSURI Ponorogo, 2022)
This article contains the results of teacher mentoring by PTIQ Jakarta Postgraduate lecturers. The implementation of this activity was motivated by the low understanding of teachers about innovative teachers, especially in the era of the Covid-19 pandemic. This service activity is expected to increase the capacity of innovative teachers which in turn improves the quality of educational institutions. The implementation method used is participatory action research (PAR). The selection of this method is considered in accordance with the target and assisted object. Participants in this training consisted of all teachers at SD Character Genius Islamic School Depok City. The results of the implementation of this mentoring show that teachers experience a poor understanding of innovative teachers which has an impact on the low quality of the learning carried out. From the results of the implementation of mentoring carried out by all teachers, they can understand well about: 1) the meaning of innovative teachers, the scope, and urgency of being an innovative teacher during the Covid-19 pandemic; 2) the teacher succeeded in creating innovative online-based learning models and media such as animated videos, contextual teaching-learning (CTL), Quizizz, and Kahoot to support the normality of online learning. The conclusion of this activity has a positive impact on teachers and institutions because they are given encouragement as well as facilities to become innovative teachers in the era of the Covid-19 pandemic.